DEVELOPMENT OF SOCIAL CONVOYS: TRAJECTORIES OF CONVOY STRUCTURE AND COMPOSITION FROM CHILDHOOD THROUGH ADULTHOOD. (20th December 2022) - Manalel, Jasmine; Cleary, Jennifer; Antonucci, Toni
Abstract: This study examines stability and change in social convoys from childhood to adulthood and variation in trajectories of convoy characteristics by gender and race. Multilevel models for convoy structure and composition were estimated using longitudinal data spanning 23 years. Respondents included a sample of 193 children aged 8 to 12 in Wave 1 (1992) who were surveyed again in their 20s (Wave 2) and 30s (Wave 3). Changes in composition, proximity, and contact frequency were observed at each wave. Between Waves 1 and 2, changes reflected age-normative trends toward network diversification typical of the transition to adulthood. Between Waves 2 and 3, changes were consistent with those expected as young adults settle into stable roles. We also identified convoy characteristics that differed between men and women and between Black and White individuals, emphasizing the importance of personal characteristics to fully understand form and function of social relations across the lifespan.